THE DYNAMICS OF THE DOW JONES SUKUK VOLATILITY: EVIDENCE FROM EGARCH MODEL - Nadhem SELMI; Mohamed FAKHFEKH; Marwa BEN SALEM (Business Excellence and Management, 2015)
This paper aims to test the effect of asymmetric shocks on the volatility of the Dow Jones Sukuk. To this end, we applied the EGARCH model to give a clear idea of the effect of asymmetric shocks on the volatility of the sukuk. Considering the daily returns of the Dow Jones Sukuk for the period from 09/06/2009 to 31/12/2013, our results suggest that the volatility of the 2009-2010 period is very sensitive to market events over the period 2010-2013 and positive shocks are more volatile than negative one. The results have important implications for the sukuk market. This result can be explained by the good transparency, disclosure and better incentives that make investors expand their business in the market for sukuk.